Competitive exchange interaction and noncollinear magnetic structure in Mn-based Ni2In type alloys. (March 2019) - You, Yurong; Xu, Guizhou; Tang, Jiaxuan; Gong, Yuanyuan; Xu, Feng
Abstract: Novel magnetic skyrmion state has recently been identified in the centrosymmetric hexagonal MnNiGa alloy, rendering it interesting for the exploration of the origin of noncollinear magnetism in MnNiGa and related Ni2 In-type MnMX alloys. In this work, we investigate the magnetic interaction and noncollinear magnetic structure in MnNiGa, MnFeGe and MnCoSn alloys, mainly by the method of first principles studies. It is revealed that in these systems, the shortest Mn-Mn separation, denoted by the parameter d 1, plays the dominant role in determining the magnetic state. The calculation of the exchange parameters Jij shows that they exhibit a competing ferromagnetic and antiferromagnetic interaction along the c axis. A noncollinear calculation that considers a canting Mn moment on the neighbour sites reveals a stable state at a specific tilting angle. Preliminary experimental results for MnFeGe1- x Sn x ( x  = 0, 0.05 and 0.1) alloys demonstrate a reduced saturated magnetization with a growing value of d 1, proving the validity of our calculation. The calculation of the magnetocrystalline anisotropy and quality factor further rationalize the possibility of hosting magnetic skyrmions or bubbles in Mn-based Ni2 In alloys. Highlights: The shortest Mn-Mn distance d 1 plays the pivotal role in determining the magnetic state in MnNiGa, MnFeGe and MnCoSn. The exchange parameters Jij were calculated and revealed competing interaction along the c axis. Noncollinear calculation confirmed the predicted canting state of MnNiGa and MnFeGe alloys. Experimental tuning of the magnetic interaction was realized by doping on different sites in MnFeGe alloy.